2022
DOI: 10.1088/1742-6596/2312/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Algorithms to Identify Distributed Denial-of-Service Attacks

Abstract: In the current pandemic situation, much work became automated using Internet of Things (IoT) devices. The security of IoT devices is a major issue because they can easily be hacked by third parties. Attackers cause interruptions in vital ongoing operations through these hacked devices. Thus, the demand for an efficient attack identification system has increased in the last few years. The present research aims to identify modern distributed denial-of-service (DDoS) attacks. To provide a solution to the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Contrary to the bagging algorithms which are parallel trained, the boosting technique, mostly homogeneous, trains a sequence of models on a weighted training set. Boosting works by sequentially adding models to the Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  Distributed denial of service attacks classification system using features selection and … (Leila Bagdadi) 1871 ensemble, each new model corrects the errors made by the previous models [37] until the performance is satisfactory or other stopping conditions are met. In contrast, stacking is an ensemble learning framework where a distinct machine learning algorithm is trained to merge the predictions of multiple ensemble members [35].…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…Contrary to the bagging algorithms which are parallel trained, the boosting technique, mostly homogeneous, trains a sequence of models on a weighted training set. Boosting works by sequentially adding models to the Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  Distributed denial of service attacks classification system using features selection and … (Leila Bagdadi) 1871 ensemble, each new model corrects the errors made by the previous models [37] until the performance is satisfactory or other stopping conditions are met. In contrast, stacking is an ensemble learning framework where a distinct machine learning algorithm is trained to merge the predictions of multiple ensemble members [35].…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…In this methodology Random Forest and MLP as a single model RF-MLP which analyses and evaluate the network traffic and establishes a security prediction model that accurately identifies DoS attack. The authors of research paper [4], uses 10-fold cross validation and found the accuracy drastically increases from 94.88% to 99.2% in just 0.48 minutes by LGBM. A limitation was found that in their work all instances present in the dataset cannot be processed.In [5], the models logistic regression, Gradient Boosting and Naive Bayes gives best evaluation metric values, used cross-Fold validation and log loss methods to identify the better models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These attributes can be divided into two groups: categorical and numerical. The categorical attributes primarily consist of destination address, source address, and utilized protocols and the remaining features are numerical type which are analyzed based on various visualization methods as shown in below figures [3][4][5][6][7][8][9][10][11][12]. error-checked delivery of data between applications over a network.…”
Section: A Datasetmentioning
confidence: 99%